PEMANFAATAN Î± â KERATIN BULU AYAM SEBAGAI ADSORPSI ION Pb DALAM LIMBAH TEKSTIL - Latifah, Rais Nur; Ernia, Roro; Yulianto, Erick Rian; Pramono, Edi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The present study was undertaken to develop a cost effective biosorbent and to study the biosorption process involved in the adsorption of heavy metal-contaminated textile wastewater using the developed biosorbent. Biomass chicken feathers was activated by Na2S 0.1 N to produce adsorbent for lead in aqueous solution. This study focuses on the effectiveness of lead removal by batch adsorption method.Â The feather samples both activated and non-activated with adsorbed Pb (II) ions were analyzed by spectroscopic methods (Surface Area Analyzer, Atomic Absorption Spectroscopy and Fourier transform infrared spectroscopy). Particularly, the effect of pH, agitation time, adsorbent concentration, and particle size were considered. Optimum adsorption pH values of Pb (II) for activated and non-activated feathers were 8 whereas optimum adsorption contact time of Pb (II) for activated and non-activated feathers were 60 minutes and 90 minutes respectively.Â At the optimal adsorption conditions, adsorption ratio could get to 97.52% for activated feathers and 98.67% for non-activated feathers. The higher concentration of lead has a greater adsorption as well as highÂ adsorptionÂ capability of feathers. The Freundlich adsorption model agrees well with experimental data, because of the high correlation coefficient that the former exhibited, thus, indicating to the applicability of multilayer coverage of the Pb (II) on the pores of adsorbent surface. The applicability of the Ho and Lagegren kinetic model has also investigated. Lead ions from the sample of textile wastewater were adsorbed on activated feathers with efficiency up to 90%. Laboratory tested and proven more effective and efficient in removingÂ Pb (II) ions from aqueous solution by using activated feathers. The low cost and simplicity of the technique hold great potential applications in environmental protection.Keywords: Adsorption; Biomass of chicken feather; Heavy metals; Pb (II) ions; Textile wastewater